2013
DOI: 10.1021/ie401535h
|View full text |Cite
|
Sign up to set email alerts
|

CuO/Graphene Nanohybrids: Preparation and Enhancement on Thermal Stability and Smoke Suppression of Polypropylene

Abstract: Cu/graphene nanohybrids were successfully prepared using a simultaneous chemical reduction method. Successful oxidation of Cu nanoparticles was carried out by the melt blending during preparation of the nanocomposites. Cu nanoparticles were well dispersed on graphene with a diameter of 3–7 nm. XRD and TGA results revealed successful oxidation of Cu nanoparticles during processing. TEM results indicated that PP nanocomposites decorated with CuO/graphene were better dispersed than those added with graphene becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Metals or metal derivative-based nanomaterials include metal oxides, metal hydroxides and other metallic compounds, such as Co 3 O 4 [106], SnO 2 [107], Ce-MnO 2 [108], TiO 2 [109,110], CuO [111], NiO [106], [114], NiCe x O y [115], ZrO 2 [116], Ni(OH) 2 [116], MnCo 2 O 4 [38], FeOOH [117], AlOOH [118], NiAl-LDH [119] (LDH represents to layered double hydroxide), NiFe-LDH [120], Co(OH) 2 [121], ZnS [122], ZnCO 3 [123], MoS 2 [124], Al(H 2 PO 2 ) 3 [125], ferrocene (Fc) [126], zirconium organophosphate [127], nano-Sb 2 O 3 [128] and zinc hydroxystannate [129,130]. They can also be classified into zero-dimensional nanoparticles, onedimensional nanowires/nanorods/nanotubes and two-dimensional nanoplates/nanobelts.…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…Metals or metal derivative-based nanomaterials include metal oxides, metal hydroxides and other metallic compounds, such as Co 3 O 4 [106], SnO 2 [107], Ce-MnO 2 [108], TiO 2 [109,110], CuO [111], NiO [106], [114], NiCe x O y [115], ZrO 2 [116], Ni(OH) 2 [116], MnCo 2 O 4 [38], FeOOH [117], AlOOH [118], NiAl-LDH [119] (LDH represents to layered double hydroxide), NiFe-LDH [120], Co(OH) 2 [121], ZnS [122], ZnCO 3 [123], MoS 2 [124], Al(H 2 PO 2 ) 3 [125], ferrocene (Fc) [126], zirconium organophosphate [127], nano-Sb 2 O 3 [128] and zinc hydroxystannate [129,130]. They can also be classified into zero-dimensional nanoparticles, onedimensional nanowires/nanorods/nanotubes and two-dimensional nanoplates/nanobelts.…”
Section: Inorganic-nanomaterials Graphene-based Composite Flame Retarmentioning
confidence: 99%
“…[1][2][3] However, PP is easily flammable, and flame retardancy becomes an essential requirement in order to expand its application. [1][2][3] However, PP is easily flammable, and flame retardancy becomes an essential requirement in order to expand its application.…”
Section: Introductionmentioning
confidence: 99%
“…nanotubes, carbon black, graphene, metallised graphene, or metallic particles, which have been shown to increase the electrical conductivity, [12][13][14][15] but increasing the thermal conductivity has proven far more difficult, 8,16 especially when considerations of corrosion and thermal resistance were also imposed, which ruled out water-soluble polymers such as PEI, where high conductivity has been reported. 17 For example, Dittrich et al, Shi et al, and Chatterjee et al have demonstrated that it is possible to increase the thermal coefficient of PP nanocomposites with graphene, 18 metal/graphene combination, 19 or graphene and other carbon particle mixtures, 20 but at the concentrations reported only a value of K , 0.3 W m 21 K 21 was achieved. Electronic conductivity can be accomplished when the percolation threshold of the particle is reached and the conducting components are at least in point contact.…”
mentioning
confidence: 99%